PENGOBATAN TRADISIONAL TOGAK BELIAN PADA MASYARAKAT KENEGERIAN KOTORAJO KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Fitri Anggela; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study on “Traditional Treatment Of Togak Belian In The Dirty Nation Of The Districts Kuantan Hilir Seberang Districts Kuantan Singingi. Where this research intends to explain how the implemention of traditional medicine is intended to explain how the treatment by the village community Dirty Nation of The Districts Kuantan Hilir Seberang Districts Kuantan Singingi what are the factors that influence people taking traditional medicine. Sunjects in this study were traditionally populated traditional in the village Kenegerian Kotorajo. Where in this research the writer uses the type of qualitive research that is research that produces descriptive data changing written or verbal words and explains data through reasoning based on ;ogic to draw logical conclusions and use the analyzed data so that it can develop a systematic situation that it can develop a syistematic situation that is appropriate to the phenomenon being in scrutiny.data collection techniques using interview techniques, observation, literature study. Based on the results of this study the community in the village Kenegerian Kotorajo stil use traditional medicine until now even they believe in traditional medicine because they have been taking medication from their ancestors from their ancestors from then until now.every treatment they take action to do the treatment of a traditional healer or chemist, because they use two traditional hearler sor chemist, because they use two traditional and medicated treatments Keywords : Perception Education and Dropust.